Фізичні основи лазерного гравіювання та його застосування в поліграфії - Сокрута, С. В. (ХНУРЕ, 2025)
Laser technologies have recently been finding increasingly widespread applications in industry, including printing. The development of modern production drives the growing implementation of high-tech solutions. Laser engraving is a universal and efficient method for applying images, text, or patterns to various materials. This type of engraving enables the creation of precise, detailed images on different materials such as wood, metal, plastic, and leather. It is an ideal solution for working with fragile materials where there is a risk of damage.
Keywords: лазер; гравіювання